Design and Development of MANETs with Quality of Service Parameters (International Journal of Engineering and Computer Science, 2015)
Mobile Ad Hoc Networks (MANETs) are a self-configuring network of mobile nodes connected by wireless links. In MANETs, each mobile node works as a host as well as a router. MANETs are used in various and varied applications like setting up of conferences, e-classrooms, patient monitoring, detection of earthquakes etc. With the growth and proliferation of these devices in every aspect of society, the need for such devices to communicate in a seamless manner is becoming increasingly essential. Also, as MANETs gain popularity, their need to support real time and multimedia applications is growing as well.  Real time and multimedia applications supported by MANETs have stringent Quality of Service (QoS) parameters such as efficient bandwidth utilization, minimum delay, minimum packet loss, good throughput etc. Providing QoS is difficult in MANETs due to a lack of centralized infrastructure based system, limited bandwidth availability, constant movement of nodes, contention for channel access and the highly dynamic topology of the wireless network. This paper is a study on the design and development of MANETs with necessary QoS parameters like low packet loss, good throughput, less delay.